Method for Optimization of a Shielding Effectiveness Measurement System Using Shielding Concrete Blocks for IEMI - Hongje Jang; Myungryul Choi; Taesueng Song; Sungwook Kim (IEEE Access, 2022)
The recent digitization of many technologies has made information communication facilities vulnerable to intentional electromagnetic interference (IEMI) and electromagnetic pulses (EMPs). Concrete with shielding capability is being studied to protect entire information facilities or security facilities from these threats. Although the conventional standards ASTM D 4935 and MIL-STD-188-125-1 provide guidelines with regard to the assessment of the shielding effectiveness (SE) of materials, these standards are not applicable to concrete owing to the thickness of concrete, particularly when reinforced with rebar, the composition of building materials, time, and cost. To solve this problem, this paper proposes a method for measuring the SE of concrete used for building construction. The proposed measuring method is based on the MIL-STD-188-125-1 standard. Small concrete blocks are used as specimens for testing the suggested SE measurement method, which is designed to operate in the frequency range of 600 MHz to 1.5 GHz. The accuracy of the proposed method is optimized by varying parameters such as the size of the concrete blocks, incidence angle of electromagnetic waves, fixture materials, and the use of absorbers. The results of the proposed method are compared with those of the ASTM D 4935 standard. The SE of concrete blocks, concrete walls, and concrete buildings is also tested using the proposed method and MIL-STD-188-125-1. Similar results were obtained with all of these methods. Therefore, the proposed method to measure the SE of concrete blocks might be suitable to ascertain that buildings constructed with the same concrete could be expected to have the same SE.